Seed-mediated growth of Au nanorings with size control on Pd ultrathin nanosheets and their tunable surface plasmonic properties. Issue 6 (27th January 2016) - Wang, Wenxing; Yan, Yucong; Zhou, Ning; Zhang, Hui; Li, Dongsheng; Yang, Deren
Abstract : Au nanorings with size control were generated by seeded growth on Pd nanosheets, which showed tunable surface plasmonic properties. Abstract : Nanorings made of noble metals such as Au and Ag have attracted particular interest in plasmonic properties since they allow remarkable tunability of plasmon resonance wavelengths associated with their unique structural features. Unfortunately, most of the syntheses for Au nanorings involve complex procedures and/or require highly specialized and expensive facilities. Here, we report a seed-mediated approach for selective deposition of Au nanorings on the periphery of Pd seeds with the structure of an ultrathin nanosheet through the island growth mode. In combination with selective etching of Pd nanosheets, Au nanorings are eventually produced. We can control the outer diameter and wall thickness of the nanorings by simply varying the size of the Pd nanosheets and reaction time. By taking the advantage of this size controllability, the nanorings show tunable surface plasmonic properties in the near infrared (NIR) region arising from both the in-plane dipole and face resonance modes. Owing to their good surface plasmonic properties, the nanorings show substantially enhanced surface-enhanced Raman spectroscopy (SERS) performance for rhodamine 6G, and are therefore confirmed as good SERS substrates to detect trace amounts of molecules.